Virulence genes in biofilm producer Enterococcus faecalis isolates from root canal infections - Akbari Aghdam, M.; Soroush Barhaghi, M. H.; Aghazadeh, M.; Jafari, F.; Beomide Hagh, M.; Haghdoost, M.; Memar, M. Y.; Ahangarzadeh Rezaee, M.; Samadi Kafil, H. (Cellular and Molecular Biology, 2017)
Enterococcus faecalis is occurring in opportunistic infections involving the oral cavity. This study aimed to evaluate the presence of E. faecalis virulence genes in dental root canal isolates recovered from advanced chronic periodontitis patients. One hundred E. faecalis isolated from dental root canal during July 2015 to Oct 2016. After analysis of biofilm formation by the semi-quantitative determination in 96-well flat bottom polystyrene plates, the presence of asa, esp, efaA, ace, ebpR, gel and hyl gene were studied by PCR. Gelatinase and hemolytic activity were detected by phenotypic methods. Ninety-one percent of isolates had ebpR gene, 85% ace, 82% efaA, 81% gel, 56% esp, 33% asa1, 2% hyl and 0% cyl gene. Evaluation of biofilm formation by microtiter plate method presented 49% of the isolates as strong biofilm producer, 42% displayed moderate biofilm formation, and 10 % weak or no biofilm was observed. asa1, efaA, esp, and ebpR positive isolates had significantly higher biofilm formation than negative isolates, while no significant differences were found when comparing ace-positive and - negative isolates. Present study showed that the ace genes do not seem to be necessary nor sufficient for the production of biofilm in Enterococcus faecalis but the presence of asa1, efaA, esp, and ebpR correlates with increased biofilm formation of dental root canal isolates.